Use of blinatumomab and CAR T-cell therapy in children with relapsed/refractory leukemia: A case series study - Wang, Songmi; Liu, Aiguo; Wang, Na; Wang, Yaqin; Zhang, Ai; Wang, Li; Yu, Wen; Li, Chunrui; Zhang, Yicheng; Hu, Qun (Frontiers in Pediatrics, 2023)
Background: The 5-year event-free survival rate for childhood acute lymphoblastic leukemia (ALL) has increased to more than 85%. However, the 5-year overall survival rate in children with relapsed/refractory ALL did not exceed 50%. In the past decade, immunotherapies (such as blinatumomab and chimeric antigen receptor T-cell therapy) were approved for relapsed/refractory B-ALL, transforming the treatment environment for children with relapsed/refractory ALL. Objective: This study aimed to explore how immunotherapy can be incorporated into salvage regimens for pediatric patients with relapsed/refractory ALL by retrospectively analyzing the diagnosis and treatment process of seven children with relapsed/refractory leukemia and observing the side effects of the two strategies and long-term survival. Methods: The clinical features and treatment responses of patients aged <14 years with relapsed/refractory leukemia who received immunotherapy (including Chimeric Antigen Receptor T cell treatment and blinatumomab) at Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology between February 2014 and April 2022 were retrospectively analyzed. Results: Seven children underwent immunotherapy. Five patients received immunotherapy and sequential allogeneic hematopoietic stem cell transplantation (HSCT), whereas the other two received only immunotherapy. Five patients achieved complete remission (71.4%). None of the patients had severe cytokine-release syndrome. However, one developed grade 3 immune effector cell-associated neurotoxicity syndrome with prior leukoencephalopathy. The median follow-up period was 541 days (range, 186–3180 days). No deaths were related to treatment. Three patients relapsed, two had CD19-negative recurrences, and the third showed CD19 antigen reduction. One patient died after disease progression, whereas the other died of HSCT-related complications. One patient abandoned the treatment after relapse and was lost to follow-up. Conclusion: Blinatumomab and CAR T-cell therapy showed excellent remission rates and manageable toxicity in pediatric patients with relapsed/refractory leukemia. However, the duration of the remission was limited. Therefore, further prospective randomized clinical studies should be conducted to improve the long-term efficacy of immunotherapy.